"Looking for Deviations": Nurses' Observations of Older Patients With COPD in Home Nursing Care. (August 2020) - Øfsti, Ruth; Devik, Siri Andreassen; Enmarker, Ingela; Olsen, Rose Mari
Nurses working in home care play a significant role in observing and identifying changes in the health status of patient with chronic obstructive pulmonary disease (COPD). The aim of this study was to explore and describe nurses' observations of older patients with COPD when providing home nursing care. In this qualitative explorative study, data were collected through observations of 17 home care visits using the think-aloud technique, followed up with individual interviews with the nurses. Qualitative content analysis was used to analyze the data. The findings showed that the nurses' observations (focus, methods, and interpretation) were characterized by their search for deviations from what they judged to be the patient's habitual state. The nurses did not use any tool or guidelines, nor did they follow a standard procedure. Instead, when observing and interpreting, they performed a complex process guided by their experience and knowledge of the patient, and the patient's individual and contextual circumstances. This knowledge contributes to warranted reflection on nurses' practice in this context to secure COPD patients' safety and quality of life.